Initial growth crown cover of cerrado species from different sucessional groups - Forlin, Tatiane; Lima, Ana Paula Leite; Lima, Sebastião Ferreira; Paula, Rita Cássia Mariano; Neto, Vespasiano Borges Paiva; Silva, Wesley Gomes (Ciência e Natura, 2022)
This study had the objective to evaluate the initial growth and crown cover of native cerrado species of different successional groups in planting forest restoration in Chapadão do Sul, MS, with an experiment installed in February of 2013 to test restoration models. Twelve species were selected, being four pioneers: Anadenanthera falcata, Cybistax antisyphilitica, Platypodium elegan and Samanea tubulosa; four early secondary species: Dipteryx alata, Sterculia striata, Alibertia edulis and Enterolobium contortisiliquum; and four late secondary species: Cedrela fissilis, Copaifera langsdorfii, Handroanthus roseo-albus and Hymenaea stilbocarpa. Diameter at soil height (DSH), total height and crown diameter were measured at 8, 14, 20 and 26 months after planting. the periodic increase in height and DSH were calculated by species, group and age, and the crown area at 26 months. The highest increases in height and DSH were from the pioneers group and from the early secondary until 26 months, and the lowest increases were from the late secondary species. The species within each group vary their initial investment in height and DSH. The pioneers group presented the largest crown areas, while the late secondary group presented the smallest.